A Methods engineering study on Gelmart Industries Philippines, Inc. - Cortez, Daniel Mark (College of Engineering, 2004)
The group during this whole study on Gelmart Industrial Philippines (GIP) focused on improving their sewing operation of brassieres-the most time and cost consuming operation. The group conducted plant visits, during which the group conversed with management and workers, observed and gathered data. Through these three primary methods, and with the help of quantitative analysis, several problems were isolated and rooted out by the group. Two major problems were discovered : lack of productivity and faulty work design. Lack of productivity was observed as bottlenecks, idle time, reworks, difficult methods, lack of worker motivation, high disparity between quota and actual times, and other problems were observed on the sewing line. Faulty work design was based on the detection of possible injury-causing equipment and workplace, noise, distracting runners, messy trash disposal system and other problems. These two major problems led to the generation of several recommendations that are directed on solving and answering these concerns. Workplace alternatives were developed like the table extension, several new fixtures, layout change, and new chair and table designs. Methods improvement was also done as location of materials, containers for raw materials, friction increasing aids, methods standardization, and use of fixtures were suggested. Policy change given are salary and incentive system improvement, standards change, job rotation, change in the allocation of worker to operation, stretching exercises, etc. These recommendations are then organized into two groups for implementation strategy : immediate and future change. Implementation plan is focused on immediate change while future changes deal with possible improvements that could be pursued by the company.These include purchasing materials, informing worker on the changes, setting policy modifications and timelines for these suggestions, and lastly, following up on all changes made.